PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN EREMERASA KABUPATEN BANTAENG - Hidayati, Andi (Indonesian Journal Of Law Studies, 2024)
Thepurposeofthis researchare: 1)Todeterminetheinfluence ofleadershipon employeeperformance attheEremerasa Sub-District, Bantaeng Â Regency,Â  2) Â To Â determine Â the Â influence Â of Â organizational cultureÂ  Â onÂ  Â employeeÂ  Â performanceÂ Â  atÂ  Â theÂ  Â EremerasaÂ Â  Sub-District, BantaengRegency,3)To determinetheinfluenceofworkdisciplineon employeeperformanceatthe Eremerasa Sub-DistrictOffice, Bantaeng Regency, 4)To determinethesimultaneous influenceof leadership, organizational culture,andworkdisciplineon employeeperformance at theEremerasa Sub-District,Bantaeng Regency, 5)Toidentifywhich variable Â hasÂ  aÂ  greaterÂ  influence Â among Â leadership, Â organizational culture, and workdisciplineon employeeperformance attheEremerasa Sub-District,BantaengRegency.The research methodemployedinthis studyis asurveymethod with aquantitativeapproach, focusingon hypothesis testing.The populationconsists of 40individuals, andthe sampleisdrawnusingacensusmethod,resulting inasamplesizeof40 respondents.Datais collectedthroughquestionnairesanddirect observation.Thedata analysisiscarriedoutdescriptivelyusing quantitativemethodswiththe SPSSprogram,utilizingmultiplelinear regressionanalysis.The researchfindingsindicatethatleadership, organizationalculture, andworkdisciplinecollectivelyhavean 84% influenceonemployee performanceattheEremerasaSub-District, Bantaeng Â Regency, Â while Â the Â remaining Â 16% Â is Â explained Â by Â otherEdy, Â Sutrisno. Â (2004). Â Manajemen Â Sumber Â Daya Â Manusia. Â Jakarta: Â KencanaPrenadaMediaGroup.Â E.Mulyasa.(2002).ManajemenBerbasisSekolah.Bandung:Rosdakarya.Â Greendberg, Â Jerald,Â  Robert Â A.Barron, Â 2005. Â Behavior Â inOrganization, Â Fourth Â Edition, AllynandBacon,USAÂ Hartati(2016).â€œPengaruhMotivasiKerja,DisiplinKerja,danKompetensi terhadapKinerja Pegawaipada DinasPengelolaanSumberDaya Air,PertambangandanEnergi KabupatenSoppengâ€.Tesis.Makassar:PascasarjanaSTIEAMKOP.Hadari,Nawawi.(2006).Kepemimpinan Â Mengefektifkan Â Organisasi.Yogyakarta:GadjahMadaUniversityPress.Â HamzahB.UnodanNinaLamatenggo.(2012).TeoriKinerjadanPengukurannya.Â Jakarta:BumiAksara.Hasibuan, Â Malayu, Â S.P. Â (2009). Â Manajemen Â Sumber Â Daya Â Manusia. Â Jakarta:GunungAgung.IvancevichJohnM,2002,PerilakudanManajemenOrganisasi,ed7,Erlangga,Jakarta. Ichlapio Â Fitrianto Â (2016), Â â€œPengaruh Â motivasi, Â disiplin, Â dan Â kepuasan Â kerja, Â terhadapkinerjakaryawanPT.BumiRamaNusantaraâ€. Â Tesis.Makassar: Â Pascasarjana Â STIE AMKOPKartini, Â Kartono. Â (2008). Â Pemimpin Â danKepemimpinan Â Apakah Â KepemimpinanAbnormalitu?.Jakarta:RajaGrafindoPersada.Â Makkira Â (2016 Â â€œPengaruh Â disiplin Â kerja, Â komitmen Â organisasi, Â dan Â lingkungan Â kerjaterhadap Â kinerja Â karyawan Â pada Â PT. Â Trans Â retail Â indonesia Â (carrefour) Â cabang35Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Â AndiHidayati,Vol.2 No.1 Juli2023 Â Mangkunegara, Â A.A.AnwarPrabu.(2001).Â  Manajemen Â SumberDayaManusiaPerusahaan.Bandung:RemajaRosdakarya.